2023
DOI: 10.1177/08927057231186326
|View full text |Cite
|
Sign up to set email alerts
|

Examination of compressive and flexural behaviors of acrylonitrile-butadiene-styrene filled with hemp fiber particles

Abstract: Effects of the addition of hemp fiber particles on the compressive and flexural behaviors of an industrially important amorphous thermoplastic, Acrylonitrile-Butadiene-Styrene (ABS), were investigated for the first time in this study. Particles with a size of 67–500 μm were first extracted from 10% NaOH alkaline-treated hemp fibers, and then incorporated into ABS at three various weight ratios (1wt%, 5wt% and 10wt%). Compression and three-point bending tests results revealed that both the compressive and flexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…218 It was reported that the addition of hemp fiber particles on the compressive behaviour of industrially important thermoplastics, namely Acrylonitrile-Butadiene-Styrene (ABS). 219 Application of nanocellulose as an adsorbent for industrial effluent treatment. Activated carbon derived from carbonized nanocellulose has undeniably excellent adsorbent properties with no adverse effects for industrial effluent treatment.…”
Section: Nanocellulose As Bio-based Materials In Various Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…218 It was reported that the addition of hemp fiber particles on the compressive behaviour of industrially important thermoplastics, namely Acrylonitrile-Butadiene-Styrene (ABS). 219 Application of nanocellulose as an adsorbent for industrial effluent treatment. Activated carbon derived from carbonized nanocellulose has undeniably excellent adsorbent properties with no adverse effects for industrial effluent treatment.…”
Section: Nanocellulose As Bio-based Materials In Various Applicationsmentioning
confidence: 99%
“…218 It was reported that the addition of hemp fiber particles on the compressive behaviour of industrially important thermoplastics, namely Acrylonitrile-Butadiene-Styrene (ABS). 219…”
Section: Source Of Nanocellulose From Natural Fibermentioning
confidence: 99%
“…9 One such innovative approach lies in the realm of natural fiber reinforcement and fabrication of thermoplastic composites. [10][11][12][13] The reinforcing properties of natural fibers, such as bamboo, have been extensively explored and established in various composite materials. [14][15][16] Bamboo fibers, renowned for their exceptional strength, lightweight nature, and eco-friendliness, offer a compelling solution to the challenges posed by recycled ABS.…”
Section: Introductionmentioning
confidence: 99%